2017
DOI: 10.1016/j.bbrep.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential usage of COX-1 and COX-2 in prostaglandin production by mast cells and basophils

Abstract: Basophils have been erroneously considered as minor relatives of mast cells, due to some phenotypic similarity between them. While recent studies have revealed non-redundant roles for basophils in various immune responses, basophil-derived effector molecules, including lipid mediators, remain poorly characterized, compared to mast cell-derived ones. Here we analyzed and compared eicosanoids produced by mouse basophils and mast cells when stimulated with IgE plus allergens. The production of 5-LOX metabolites s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
0
22
0
2
Order By: Relevance
“…Further, the severity of IBS-D with abdominal pain is directly proportional to the amounts of prostaglandin E2 (PGE2) released [17,18]. A key step involving in PGE2 production is the conversion of arachidonic acid to prostanoids catalyzed by cyclooxygenase-1 and-2 (COX-1, COX-2) [19]. Previous study have shown that 6-gingerol can inhibit the production of PGE2 and inflammation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the severity of IBS-D with abdominal pain is directly proportional to the amounts of prostaglandin E2 (PGE2) released [17,18]. A key step involving in PGE2 production is the conversion of arachidonic acid to prostanoids catalyzed by cyclooxygenase-1 and-2 (COX-1, COX-2) [19]. Previous study have shown that 6-gingerol can inhibit the production of PGE2 and inflammation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation is associated with factors like reactive species of oxygen and nitrogen, cytokines, chemokines, growth factors, and specific microRNAs, which often contribute to cancer development [19]. In most epithelial cells, COX-2 is absent or expressed at low levels but is a major contributor to inflammation and is up-regulated in many cancers, [20], so it is a relevant therapeutic target for cancer prevention and treatment [10,11,12,13]. Studies in K14-HPV16 mice have demonstrated that COX-2 is overexpressed in skin lesions induced by the HPV16 early genes [20].…”
Section: Discussionmentioning
confidence: 99%
“…HPV-induced multiphase carcinogenesis is often associated with chronic inflammation, and experimental studies in HPV transgenic mice suggest that inflammatory phenomena play an essential role in the development of intraepithelial and invasive lesions [9]. Cyclooxygenase-2 (COX-2), a key mediator of inflammation, is involved in the development of multiple types of cancer, such as colon cancer, making it a useful therapeutic target [10,11,12,13]. We have previously shown that a specific COX-2 inhibitor, celecoxib, was able to block the progression of HPV16-induced lesions in transgenic mice [14].…”
Section: Introductionmentioning
confidence: 99%
“…Both human and mouse basophils rapidly synthesize cysteinyl leukotriene C 4 (LTC 4 ) through the 5-lipoxygenase pathway (83). There is evidence that mouse basophils metabolize arachidonic acid through cyclooxygenase activity to form prostaglandin D 2 (PGD 2 ) and prostaglandin E 2 (PGE 2 ) (72,84). In contrast, there is currently no solid evidence that highly purified human basophils can produce measurable levels of PGD 2, or any other lipid mediator generated through the cyclooxygenase pathway (85).…”
Section: Proinflammatory and Immunoregulatory Mediators/cytokines Relmentioning
confidence: 99%
“… ND, not done . a Several key surface markers are used to characterize human [IgE + , FcεRI + , CCR3 + , (CD123)IL-3Rα + , CD63 + , CD203c + ] ( 15 , 36 , 57 , 61 , 71 ) and murine basophils (FcεRI + , KIT − , CD49b + , CD200R3 + ) ( 35 , 62 , 72 76 ) by flow cytometric analysis . b This table essentially includes the phenotypic characteristics of peripheral blood human and mouse basophils.…”
Section: Proinflammatory and Immunoregulatory Mediators/cytokines Relmentioning
confidence: 99%